Controlling the type and the form of chip when machining steel - Gruby S. V.; Lasukov A. A. Aleksandr Aleksandrovich; Nekrasov R. Yu.; Politsinsky E. V. Evgeny Valerievich; Arkhipova D. A. (2016, 2016)
Title screen